Educational program on buccal health for mothers of preschool age children. - Tania Menguez Becerra; Nora Sexto Delgado; Yoel González Beriau (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Since buccal diseases are no mortal, people often fail to notice their importance. This kind of diseases appear at very early stages, however, it is possible to avoid them teaching correct behaviors in the familiar context. Objective: to prove the effectiveness of an educational intervention strategy for mothers of preschool age children. Method: A cuasi-experimental, educational intervention study was developed to modify buccal health knowledge in 40 mothers of preschool children (between 4 and 5 years), from Cruces municipality, since January 2006 and November 2007. We applied a survey to assess buccal health knowledge before and after the educational intervention, through the analysis of variables such as: brushing frequency and way, sugar diet, deforming habits, dentist consultations, breastfeeding and concern about child´s buccal health. The educative buccal health program was enforced with educational and affection-inclusive techniques complemented with didactic games as feedback. Results: Buccal health knowledge of surveyed mothers significantly increased after the intervention. Conclusions: The evaluation at the end of the program proved the effectiveness of this initiative for the acquisition and modification of knowledge related with buccal health care.